Sustainability Of Kampung Hijau Keputih Tegal Timur to The Concept of Sustainable Development - Annisa Fikriyah Tasya; Ade Fitriyanti Ulul Azmi; Tri Wahyu Diana (Center for Scientific Publication, 2020)
Surabaya as one of the cities in Indonesia that is developing towards a smart city. One of the supporting parts in sustainable urban development is settlement, both formal and informal. Kampung Hijau Keputih Tegal Timur, is used as the object of a case study to discuss the sustainable development of residential cities in Surabaya. This kampung was chosen because it has implemented several aspects of sustainability. This research was conducted to identify and assess the condition of Kampung Hijau Keputih Tegal Timur based on the sustainable development goals (SDG), and environmental & urban settlement concerns which are used as indicator. The results showed that Kampung Hijau Keputih Tegal Timur has fulfilled almost all aspects of the indicators of sustainable development goals and environmental concern & urban settlements. However, there are some unfulfilled indicators between